2023
DOI: 10.1097/sla.0000000000005883
|View full text |Cite
|
Sign up to set email alerts
|

Severity Grading Systems for Intraoperative Adverse Events. A Systematic Review of the Literature and Citation Analysis

Abstract: Introduction:The accurate assessment and grading of adverse events (AE) is essential to ensure comparisons between surgical procedures and outcomes. The current lack of a standardized severity grading system may limit our understanding of the true morbidity attributed to AEs in surgery. The aim of this study is to review the prevalence in which intraoperative adverse event (iAE) severity grading systems are used in the literature, evaluate the strengths and limitations of these systems, and appraise their appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…A previous systematic review demonstrated that classification systems are not properly utilized in the literature 1 . Despite the existence of several published guidelines to standardize complication reporting, only 25% of studies report at least half of the minimum requirements for complication reporting 1 , 17 , 27 , 38 , highlighting a need for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review demonstrated that classification systems are not properly utilized in the literature 1 . Despite the existence of several published guidelines to standardize complication reporting, only 25% of studies report at least half of the minimum requirements for complication reporting 1 , 17 , 27 , 38 , highlighting a need for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Aims . Although there are various intraoperative grading and classification systems [ 8 ], informally referred to as: EAUiaiC, iAE severity classification scheme, Modified Satava, EAES Grading system, and ClassIntra® (previously known as CLASSIC), the documentation of these iAEs is still extremely rare. Additionally, while postoperative adverse events are commonly reported, only a small portion of surgical literature addresses intraoperative complications as noteworthy outcomes [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decade, different grading systems have been introduced to capture iAEs [ 8 , 9 ] However, their adoption has been limited, and the lack of consensus across specialties necessitates external assessments [ 8 ]. Additionally, the absence of a clear, standardized definition of iAEs and their effects on postoperative courses has led to inconsistency in reporting.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis has become an indispensable tool in medical research due to its ability to provide a quantitative evaluation of scientific publications ( Jain et al, 2023 ; Kokol, 2023 ; Sayegh et al, 2023 ). This method involves the use of mathematical and statistical techniques to analyze various aspects of scholarly literature.…”
Section: Introductionmentioning
confidence: 99%